1992
DOI: 10.1203/00006450-199202000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis is Distinct at Each Stage of Ontogeny

Abstract: ABSTRACT. In vitro erythropoiesis from fetuses, newborn infants, and adults was compared in methyl cellulose cultures. Fetal and newborn blood erythroid colony formation tended to be more sensitive to erythropoietin than adult. The day of maximal colony formation was earlier in fetal than in newborn or adult cultures. The number of colonies/100 000 mononuclear cells on d 13 of culture and on the day of peak growth was highest in fetal, intermediate in newborn, and lowest in adult cultures. Burst forming units-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The results with several different techniques have already been reported (7)(8)(9)(11)(12)(13)(14). The first report was from Lo et al (9), who cultured in vitro fetal hematopoietic precursors present in the isolated mononuclear cell fraction of peripheral maternal blood.…”
Section: Discussionmentioning
confidence: 98%
“…The results with several different techniques have already been reported (7)(8)(9)(11)(12)(13)(14). The first report was from Lo et al (9), who cultured in vitro fetal hematopoietic precursors present in the isolated mononuclear cell fraction of peripheral maternal blood.…”
Section: Discussionmentioning
confidence: 98%
“…Stem cells are characterized by the expression of the CD34 + cell-surface antigen [37][38][39]. Some studies have demonstrated the fetal blood presents a higher frequency of hematopoietic progenitors than adult peripheral blood [39].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will focus on maternal cell suppression and selective "in vitro" culture of fetal cells. Investigations into the best culture time for fetal CD34 + cell growth [29,38], supplements for culture media [41,42], and biological differences between fetal and maternal cells appear to be the most promising approaches [18,43].…”
Section: Discussionmentioning
confidence: 99%
“…These include in vivo differentiation almost exclusively along the erythroid pathway (see p. 51 in ref. 30), rapid cycling rate and accelerated in-vitro maturation time (31), greater sensitivity to erythropoietin (31)(32)(33), and decreased sensitivity to GM-CSF (34). In vivo, FL hematopoiesis is almost entirely restricted to the erythroid lineage.…”
Section: Discussionmentioning
confidence: 99%